1992
DOI: 10.1038/bjc.1992.44
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and specificity of CA242 in gastro-intestinal cancer. A comparison with CEA, CA50 and CA 19-9

Abstract: Summary A serological assay for the quantitative determination of the novel tumour-associated epitope CA242 was developed and used for determination of sensitivity and specificity of CA242 in gastrointestinal cancer. The CA242 assay showed a better tumour specificity than CA50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
67
0
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(80 citation statements)
references
References 21 publications
8
67
0
3
Order By: Relevance
“…When used in combination with CEA, CA-19-9 (Quentmeier et al, 1987) and (Sagar et al, 1991;Ruggeri et al, 1993) have been shown to provide a gain of positivity in colorectal cancer. The recent studies of showed that it has a higher sensitivity than CA-50 in primary colorectal cancer and a low false positivity in benign liver disease (Kuusela et al, 1991;Nilsson et al, 1992). In prinary colorectal cancer, additional use of CA-242 improves the diagnostic sensitivity of CEA alone (though it still remains limited) (Roberts et al, 1992), and CA-242 has also been shown to compklment CEA monitoring of patients reiing chemotherapy for liver metasta from colorectal cancer (Ward et al, 1993 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When used in combination with CEA, CA-19-9 (Quentmeier et al, 1987) and (Sagar et al, 1991;Ruggeri et al, 1993) have been shown to provide a gain of positivity in colorectal cancer. The recent studies of showed that it has a higher sensitivity than CA-50 in primary colorectal cancer and a low false positivity in benign liver disease (Kuusela et al, 1991;Nilsson et al, 1992). In prinary colorectal cancer, additional use of CA-242 improves the diagnostic sensitivity of CEA alone (though it still remains limited) (Roberts et al, 1992), and CA-242 has also been shown to compklment CEA monitoring of patients reiing chemotherapy for liver metasta from colorectal cancer (Ward et al, 1993 …”
mentioning
confidence: 99%
“…It is evident that while CEA monitoring during the followup of patients after potentially curative surgery is valuable it lacks the sensitivity and specificity to be an infallible guide to the patient's status (Northover, 1986 (Holmgren et al, 1984), CA-19-9 (Del Villano et al, 1983), (Barghava et al, 1987) and CA-242 (Nilsson et al, 1992), all of which have been shown to be valuable in pancreatic cancer (Kuusela et al, 1991;Taylor et al, 1992;Pasanen et al, 1993) and have been suggested as markers in colorectal cancer. When used in combination with CEA, CA-19-9 (Quentmeier et al, 1987) and (Sagar et al, 1991;Ruggeri et al, 1993) have been shown to provide a gain of positivity in colorectal cancer.…”
mentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) is the best known and most widely used of the markers (Minton et al, 1985;Staab et al, 1985;Wanebo et al, 1989), but in recent years the production of monoclonal antibodies against colorectal cancer-associated mucin antigens have allowed the detection of a further series of markers. These include CA 19-9, CA-50, (Hammarstrom, 1985;Gupta et al, 1987;Safi et al, 1987;Sagar et al, 1991;Nilsson et al, 1992). Although none of these markers has proved to be of any particular value in screening for the disease, CEA is commonly used to assess the progress of patients following surgical treatment (Minton et al, 1985) and remains the 'gold standard'.…”
mentioning
confidence: 99%
“…All three markers were elevated in 70% and at least one elevated in 93%. (Hammarstrom, 1985;Gupta et al, 1987;Safi et al, 1987;Sagar et al, 1991;Nilsson et al, 1992). Although none of these markers has proved to be of any particular value in screening for the disease, CEA is commonly used to assess the progress of patients following surgical treatment (Minton et al, 1985) and remains the 'gold standard'.…”
mentioning
confidence: 99%
“…Because of a low sensitivity in early stages of colorectal cancer, CEA is not an ideal marker for preoperative diagnosis (Brummendorf et al, 1985;Roberts, 1988;Kuusela et al, 1991;Nilsson et al,1992). However, CEA shows high sensitivity for recurrent colorectal cancer.…”
mentioning
confidence: 99%